Discovery of a Bacterial Glycoside Hydrolase Family 3 (GH3) β-Glucosidase with Myrosinase Activity from a Citrobacter Strain Isolated from Soil - Albaser,A; Kazana,E; Bennett,MH; Cebeci,F; Luang-In,V; Spanu,PD; Rossiter,JT (Journal of Agricultural and Food Chemistry, 2016)
A Citrobacter strain (WYE1) was isolated from a UK soil by enrichment using the glucosinolate sinigrin as sole carbon source. The enzyme myrosinase was purified using a combination of ion exchange and gel filtration to give a pure protein of approximately 66 kDa. The N-terminal amino acid and internal peptide sequence of the purified protein were determined and used to identify the gene, which, based on InterPro sequence analysis, belongs to the family GH3, contains a signal peptide, and is a periplasmic protein with a predicted molecular mass of 71.8 kDa. A preliminary characterization was carried out using protein extracts from cell-free preparations. The apparent KM and Vmax were 0.46 mM and 4.91 mmol dm–3 min–1 mg–1, respectively, with sinigrin as substrate. The optimum temperature and pH for enzyme activity were 25 °C and 6.0, respectively. The enzyme was marginally activated with ascorbate by a factor of 1.67.